Analisis Hubungan Pemberian ASI Eksklusif dan Pendidikan Ibu terhadap Perkembangan Bayi - Dewi Sartika Siagian; Sara Herlina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the relationship of exclusive breastfeeding and mother's education on infant development. This research is a quantitative observational analytic with cross sectional design. The results of univariate analysis show that most babies get exclusive breastfeeding as many as 46 people (55.4%), low education as many as 56 people (67.5%) and most of the normal development of 47 people ( 56.6%). The results of bivariate analysis of exclusive breastfeeding for infant development by chi square test obtained P value <0,000. Conclusions, there is a relationship between exclusive breastfeeding on infant development and bivariate analysis of maternal education on infant development. There is a relationship between mother's education and infant development. Keywords: Exclusive ASI, Mother's Education, Infant Development